From Active Data Management to Event-Based Systems and More Papers in Honor of Alejandro Buchmann on the Occasion of His 60th Birthday - Sachs, Kai.; Petrov, Ilia.; Guerrero, Pablo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Data management has evolved over the years from being strictly associated with database systems, through active databases, to become a topic that has grown beyond the scope of a single field encompassing a large range of subjects, such as distributed systems, event-driven systems, and peer-to-peer and streaming systems. The present collection of works, which sheds light on various facets of data management, is dedicated to Prof. Alejandro Buchmann on the occasion of his 60th birthday. His scientific path looks back on more than thirty years of successful academic life and high-impact research. With this book we celebrate Prof. Buchmann's vision and achievements.
Data Management, Streams and XML -- Key Concepts for Native XML Processing -- Efficient Decision Tree Re-alignment for Clustering Time-Changing Data Streams -- REaltime ACtive Heterogeneous Systems - Where Did We Reach After REACH? -- Aspects of Data-Intensive Cloud Computing -- Event Processing -- A Web That Senses and Responds -- Spatial Perspectives in Event Processing -- Implementing a Practical Spatio-Temporal Composite Event Language -- Design and Implementation of the Rebeca Publish/Subscribe Middleware -- Quality of Service and Real-Time Systems -- Anonymous Mobile Service Collaboration: Quality of Service -- SParK: Safety Partition Kernel for Integrated Real-Time Systems -- On Scientific Experiments and Flexible Service Compositions -- Peer-to-Peer -- Peer-to-Peer Web Search: Euphoria, Achievements, Disillusionment, and Future Opportunities -- Designing Benchmarks for P2P Systems -- Distributed SQL Queries with BubbleStorm -- Pervasive Computing -- From the Internet of Computers to the Internet of Things -- Distributed Group Communication System for Mobile Devices Based on SMS -- Towards Declarative Query Scoping in Sensor Networks -- Performance Engineering -- QPME 2.0 - A Tool for Stochastic Modeling and Analysis Using Queueing Petri Nets -- A Logistics Workload for Event Notification Middleware -- Business Intelligence -- Live Business Intelligence for the Real-Time Enterprise.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Algorithm Analysis and Problem Complexity